Analisis Penggunaan Aplikasi Kahoot Terhadap Tingkat Berpikir Kritis Peserta Didik Sekolah Dasar Pada Mata Pelajaran Matematika - Al Aziz, Fauzan; Dwiyanti, Ni Nengah Mega; Satriana, Rara; Supriyadi, Supriyadi; Hermawan, Jody Setya (Innovative: Journal Of Social Science Research, 2024)
The Kahoot application, used as a learning medium, can enhance students' interest in learning, making it easier for them to absorb the material presented by educators. This study aims to analyze the use of the Kahoot application in improving critical thinking skills among elementary school students, particularly in mathematics. By employing a literature review research method, this study gathers and evaluates various sources that discuss the effects of using Kahoot as an interactive learning medium. The findings indicate that the Kahoot application is effective when combined with specific models, methods, and strategies, significantly impacting critical thinking skills, independence, and motivation to learn among students.